THE STUDY OF OLD KURDISH POEMS IN KURDISH LITERATURE: بەرجەستەكرنا هـؤنـەرىَ جـوانـكـاريـێ د مـەتـەلا فۆلكلۆريـا كـورديـدا - Ahmed, Huda Sadeeq; Ahmed, Khalida Sadeeq (Journal of Duhok University, 2018)
Riddle is a significant literary art of nation, setting up the form of parse and having a great power of expression. It incorporates a partial of fine a arts that becomes a bridge of the super world of aesthetic art to show the beauty in the yarn weaved in the folklore of riddle. Fully colorful, whether in speech or meaning to show beauty in the demonstration of riddle. the elegance and decoration of riddle put it in an effective literary format and this gives the speech power full of aesthetic semantic expression by beautifying vocabulary. The existence of riddles in literature shows salient creativity of the nation and making its level of semantic expression very significant.